Knowledge, Awareness, Attitude and Behaviour about Prosthodontic Treatment for Missing Teeth among Indian Population: A Cross Sectional Study - Aradya, Anupama; Dhakshaini, M. R.; Swamy, K. N. Raghavendra; Chowdhary, Ramesh; Ranganatha, Narahari; Alla, Rama Krishna (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Purpose: The purpose of this study was to evaluate the level of awareness, knowledge, attitude and behaviour of the population aged 16-84 years toward the presence of missing teeth and prosthodontics treatment options available for replacing those missing teeth. Study Selection: A pre-structured multiple-choice questionnaire consisting of socio-demographic questions was given to 300 patients randomly after obtaining their informed consent. The questions included in the survey helped to assess the patient's level of knowledge and awareness of the prosthodontic treatment as a whole. Results: All the age group population were aware of missing teeth in their mouth and are aware of the replacement of those missing teeth. Among subjects, with a degree qualification, 18% choice of removable, 38.5% choice was fixed partial denture, and the other 38.5 % choice was implant option. For 61.6% of the elder group, 47.6% of the middle age group, and 32.7% of the younger adults, friends and relatives were the sources of information. Conclusion: This study found that patients' understanding, and awareness of prosthodontic treatment had improved. Removable dentures were the treatment option of choice for the geriatric age group when considering prosthodontic treatment alternatives. Higher-educated individuals opted for fixed dentures and implants as treatment choices.